A comparison of mandible preservation method and mandibulotomy approach in oral and oropharyngeal cancer: A meta-analysis. (December 2016) - Pang, Pai; Li, Rui-Wu; Shi, Jing-Pu; Xu, Zhong-Fei; Duan, Wei-Yi; Liu, Fa-Yu; Huang, Shao-Hui; Tan, Xue-Xin; Sun, Chang-Fu
Highlights: There is no difference in surgical margins, overall survival rate of MPM versus MLA. There is no difference in total and local recurrence rates of MPM versus MLA. There is no difference in functional outcomes like speech of MPM versus MLA. MPM provides a significant lower rate of fistula formation after surgery. Abstract: Objective: This study aims to compare the prognoses outcomes of mandibular preservation method (MPM) and the mandibulotomy approach (MLA) in oral and oropharyngeal cancer (OOPC) patients. Method: We searched PubMed, Web of Science, EMBASE, Chinese BioMedical Literature Database (CBM), Cochrane Library, and clinicaltrials.gov up to September 2016 to identify the studies that compared the prognoses of the MPM versus the MLA in OOPC patients. Two authors individually extracted the data and performed quality assessment. The surgical margins, overall survival rate, total and local recurrence rates, fistula formation, and other functional outcomes were evaluated. Result: Six studies with 309 patients were included in our analysis. No significant difference was found regarding the surgical margins, overall survival rate, total and local recurrence rates, and speech and tongue movement between the MPM and MLA groups. However, the MPM group showed a significantly lower fistula formation rate than the MLA group after the operation. Conclusion: These findings suggest that the MPM may provide a similar clinical outcome to the MLA, but that the MPM has a lower complication rate in the treatment of OOPC patients.